Analysis of Fmr1 Deletion in a Subpopulation of Post‐Mitotic Neurons in Mouse Cortex and Hippocampus. Issue 1 (9th January 2014) - Amiri, Anahita; Sanchez‐Ortiz, Efrain; Cho, Woosung; Birnbaum, Shari G.; Xu, Jing; McKay, Renée M.; Parada, Luis F.
<x xml:space="preserve">Abstract</x> Fragile X syndrome (FXS) is the most common form of inherited mental retardation and the leading cause of autism. FXS is caused by mutation in a single gene, FMR1, which encodes an RNA‐binding protein FMRP. FMRP is highly expressed in neurons and is hypothesized to have a role in synaptic structure, function, and plasticity by regulating mRNAs that encode pre‐ and post‐synaptic proteins. Fmr1 knockout (KO) mice have been used as a model to study FXS. These mice have been reported to show a great degree of phenotypic variability based on the genetic background, environmental signals, and experimental methods. In this study, we sought to restrict FMRP deletion to two brain regions that have been implicated in FXS and autism. We show that ablating Fmr1 in differentiated neurons of hippocampus and cortex results in dendritic alterations and changes in synaptic marker intensity that are brain region specific. In our conditional mutant mice, FMRP‐deleted neurons have activated AKT‐mTOR pathway signaling in hippocampus but display no apparent behavioral phenotypes. These results highlight the importance of identifying additional factors that interact with Fmr1 to develop FXS. AutismRes 2014, 7: 60–71. © 2013 International Society for Autism Research, Wiley Periodicals, Inc. © 2013 INSAR/Wiley Periodicals, Inc.